Role of Immunological Monitoring in Burns Patients - Prasanna, Mita; Singh, Kuldeep; Nagesh, S A (Indian Journal of Plastic Surgery, 1994)
The immunological parameters of 30 patients admitted within 6 hours of burns injury were compared with those of controls. Serum levels of immunoglobulins (IgG, IgA, IgM), complements (C3 & C4) and proteins (total & albumin) were estimated on admission and two weeks later in surviving patients. The aim of this prospective study was to find out the clinical importance of immunological monitoring in burns patients. It was observed that the initial fall and rebound increase in C3 and C4 levels were found to be highly significant.We conclude that IgA, IgG, C3 and C4 monitoring can help in predicting prognosis of burns patients. Base on the immunological parameters initially in nonsurvivors and two weeks later in surviving patients we can say hypothetically that prophylactic or therapeutic administration of immunoglobulins for their general or specific role could bring hopes for burns patients in future.